Optimalisasi Penguasaan Kosakata Bahasa Arab Melalui Penerapan Metode Demonstrasi - Ahmad Thohijuhdy Robi'iy Robi'iy; Ali Wafa Ali Wafa (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to evaluate the effectiveness of using the demonstration method in improving Arabic vocabulary mastery among eighth-grade students (Class VIII F) at MTsN 4 Kota Surabaya. The focus of this research arises from the issue of less interactive learning, as teachers often rely on lecture-based methods that fail to sufficiently motivate students and do not provide concrete learning experiences. The study employed a quantitative approach involving 32 students through the administration of pretest and posttest assessments. The data were analyzed using the Shapiro–Wilk normality test, Levene’s homogeneity test, paired t-test, and Cohen’s d effect size calculation. The results indicate that the data meet the assumptions of normality and equal variances. The paired t-test revealed a highly significant improvement between the scores before and after the application of the demonstration method (p < 0.001), while the effect size value of 5.20 signifies a very strong influence. In addition to the increase in test scores, observations showed positive changes in students’ learning behavior; they appeared more enthusiastic during demonstrations, more focused when the teacher presented the material, and more confident in asking and answering questions. Students also became more active in applying new vocabulary through practical exercises, creating a more dynamic learning environment compared to before. Overall, the findings confirm that the demonstration method is not only effective in enhancing learning outcomes but also successful in increasing students’ motivation, participation, and engagement in Arabic language learning.